Coaching confidential : inside the fraternity of NFL coaches - Myers, Gary, 1954 July 1- (Crown, 2012)
A chronicle of a year in the life of a composite version of an NFL head coach, including the draft, free agency, big trades, training camp, family crises, player troubles, coaching burnout, relationships with quarterbacks, staff members, and owners, rivalries, and the playoffs.